Management of Finance, Bookkeeping and Economic Development of Pre-School Education as One of the Functional Directions of Managerial Activity - Leonida Pisots’ka (Pedagogical Discourse, 2012)
Main tasks of functional direction in finance management, bookkeeping, and economic development of pre-school education in the context of management of regional authority of management of education, and management of pre-school educational establishment have been summarized in the article. These tasks have been formed on the basis of implementation of legislative-normative educational basis.